Seizure and Elinical Outcomes After Frontal Lobectomy Stratified by Anatomic Resection. (16th November 2020) - Whiting, Alex; Li, Manshi; Morita, Marcia; Whiting, Benjamin B; Wang, Xiaofeng; Bingaman, William E; Jehi, Lara
Abstract: INTRODUCTION: Literature regarding outcomes after frontal lobectomy for medically refractory epilepsy (MRE) lags significantly behind temporal lobectomy outcomes literature. METHODS: All patients who underwent a frontal lobectomy for MRE between 2010 and 2018 were retrospectively reviewed regarding demographic data, seizure outcomes, and functional outcomes. Pre-operative and post-operative MRIs were reviewed regarding category of surgery, laterality of surgery, and specific anatomic regions resected. Patients were excluded for prior surgeries, incomplete length of follow-up, surgery involving other areas of the brain, and incomplete imaging follow-up necessary for volumetric review. Frontal lobectomies were stratified based on post-operative MRI into three categories: complete premotor frontal lobectomy (PML), subtotal frontal lobectomy (SFL, greater than two anatomic regions), and partial frontal lobectomy (PFL, less than two complete anatomic regions). RESULTS: 90 patients met inclusion criteria. Fifty of 90 (55.5%) patients who underwent a frontal lobectomy demonstrated Engel I outcomes at a mean follow-up time of 3.52 (std. dev. 2.46) years. Ten of 16 (62.5%) patients who underwent PML had Engel I outcomes, 24 of 47 (51.1%) patients who underwent SFL had Engel I outcomes, and 16 of 27 (59.3%) patients who underwent PFL had Engel I outcomes. No significant difference was found in seizure outcomes in patients undergoing complete premotor, subtotal, or partial frontal lobectomies. Univariate analysis of various clinical and demographic variables found no significance in relation to seizure outcomes. Of note, 13 of 16 (81.3%) and 3 of 16 (18.8%) premotor lobectomy patients demonstrated hemiparesis immediately after surgery and at 6 month follow-up, respectively. CONCLUSION: Appropriately screened patients with MRE can achieve good seizure outcomes with both large premotor lobectomies and smaller, tailored partial lobectomies. Frontal lobectomies, in particular premotor lobectomies, have a relatively high rate of post-operative hemiparesis, with some patients still demonstrating hemiparesis at 6 month follow-up.